plz answer this que given in picture
we anybody knows how to do it
Attachments:
![](https://hi-static.z-dn.net/files/d8a/05c8087b2e9a6a15e71a974e2832d092.jpg)
Answers
Answered by
2
Answer:
The answer is given below.
Step-by-step explanation:
Use sine formula ,
∴sinA = ak
sinB = bk
sinC = ck
Also sin(A - B) = sinA.cosB - cosA.sinB
= akcosB - cosA.bk
= K(acosB - bcosA}
Similarly, sin(B - C) = k(bcosC - ccosB)
sin(C - A) = k(ccosA - acosC)
LHS = asin(B- C) + bsin(C - A) + csin(A - B)
= ak(bcosC - ccosB) + bk(acosC - ccosA) + ck(acosB - bcosA)
= k(bccosA - bccosA) + k(accosB - accosB) + k(abcosC - abcosC)
= 0 + 0 + 0 = 0 = RHS
Similar questions